Quality of LiFe (QOL) Assessment Among Advance Cancer Patient Undergoing Palliative Treatment in Malaysia - Wanda Kiyah George Albert; Adi Fahrudin (Asian Social Work Journal, 2017)
The community's stigma towards advanced cancer patients at the final stages of cancer ending up with this death, has deny their need and right to receive the best service and treatment at the end of their lives. Although there was abundant research on cancer patient issues, but there was still lack of research that focusing on final stage of cancer patients in Malaysia. This cross-sectional study is done to gives overall picture of quality of life (QOL) among final stage of cancer patient and to identify the factor that differentiate the score of QOL for the final stage of cancer patients that receiving palliative treatment at the one medical centres in Kuala Lumpur. The cross-sectional study that has been done with 120 of cancer patients that receiving palliative treatment using convenience sampling. The SF-36 questionnaire has been used to measures Quality of Life (QOL) across eight domains based on physically and emotionally component summary. Results showed that the highest score of QOL were observed in the Mental Component Summary (44.93±6.84) compared with Physical Component Summary at (42.24± 7.91). There is a difference in QOL based on mental and physical component especially from patient social demography. Mental component score have difference in term of age (t = - 0.38; p <0.001), type of cancer (F = 5.522: p <0.001), duration of treatment (t = 5.15; p < 0.001), type of treatment (F = 3.11; p = 0.029) and amount of financial support (F = 7.16; p <0.001). Meanwhile, score for physical component composite has shown difference of score based on level of education (F = 6.21; p <0.001), type of cancer (F = 5.96; p <0.001) and also amount of financial support (F = 3.00; p = 0.033). Further study should be conducted in social work perspective to identify other factors that contribute to the patient QoL and identify problems that prevent them from getting social service, so that the service given by social worker can be improved.